Implementasi Prinsip Agile Governance Melalui Aplikasi PIKOBAR di Provinsi Jawa Barat - Farhan Rahmawan Halim; Feni Astuti; Khaerul Umam (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
The research was conducted with the aim to learn about the implementation of the 3 (three) agile governance principles during the Covid-19 pandemic at the West Java Provincial Government through the application of the Pikobar application. Agile governance is expected to organize governance faster in the face of various challenges and dynamic environmental conditions. Researchers used qualitative research with the study of literature. Researchers traced a variety of secondary data sources which were then processed to be described as literature studies. Researchers conducted data analysis in accordance with the theory of agile governance proposed by Luna et al, (2015). The researcher focused the research on 3 (three) principles of agile governance. The results showed that the implementation of agile governance in the West Java provincial government did not support the maximum. This application still needs to be improved Pikobar Application. Reviewing the results of an analysis of the principle of agility of governance which is expected to be one of the efforts to improve services to the community and provide convenience in relation to the future in the health sector as it is today. Keywords: agile governance, public service, pikobar aplication